Torsional prestrain gradient and size dependence of initial yield for <100> Cu-Mn single crystals in tension - Eleftheriadis Iordanis; Neuhäuser Hartmut; Aifantis Elias C. (Journal of the Mechanical Behavior of Materials, 2012)
The effect of torsional prestrain gradient on the size dependence of initial yielding during subsequent tension of Cu-Mn single crystals is investigated experimentally.